THE RELATIONSHIP BETWEEN CHRONIC LEAD ACETATE EXPOSURE AND HYPERTENSION IN RAT - Gh. Karimi; A. Khoshbaten.; A.R. Dehpour--.; M. Abdollahi M. Sharifzadeh (Acta Medica Iranica, 1999)
Effects of 28 days lead acetate (IOC, 500, 1000 ppm) treatment on hypertension ami relationship between blood lead levels and hypertension in male. Spraguc-Dawley rats were studied. Results of this study showed tlxat lead acetate treatment did run decrease, body wcight or water consumption, except for lead acetate (1000 ppm) and sodium acetate (500 ppm) which increased fluid consumption when compared with controls. Tlte doses of lead acetate (100, 500, lOOOppm) used in this study, caused blood concentrations of 26.84 ± 2.23, 43.12+2.40 and 52.8 ±3.44 g/dl respectively. Treatment of animals with different doses (100, 500, 1000 ppm} of lead acetate Jor 28 days, caused a significant change (P< 0.05) in systolic blood pressure when compared to control rats. No dose dependent correlation was observed between blood pressure elevation and blood lead levels in treated rats.